Electrochemical and IR spectroelectrochemical studies of ligand binding to the metal centres of nitrogenase - Paengnakorn, P (2014)
Nitrogenase is a metalloenzyme that plays a key role in biological nitrogen fixation by catalysing the reduction of dinitrogen to ammonia. Study of nitrogenase is particularly challenging because of its unique electron transfer and catalytic components. This Thesis describes the development of a mediated electron transfer system for the MoFe protein of nitrogenase, in order to overcome the complexity of electron transfer by the native reductant Fe protein coupled to hydrolysis of ATP. A series of redox mediators was employed including EuIII/II-polyaminocarboxylate complexes, which have reduction potentials in a very negative range. In the presence of the redox mediators, the wild type MoFe protein exhibits a catalytic current due to protein-catalysed proton reduction. With this mediated electron transfer method, the potential of proton reduction by nitrogenase was determined for the first time. The redox mediator system was also applied in an infrared (IR) spectroelectrochemical study of CO binding to the wild type and β-98His variant MoFe protein. The first IR evidence was provided for ATP-independent CO binding to the active site of the MoFe protein, in both the wild type and the variant. The peak wavenumbers and time-dependent changes in intensity found in this study are consistent with the result of previous CO coordination with nitrogenase obtained by electron transfer from the Fe protein driven by ATP. This strongly suggests that this mediated electron transfer approach can deliver low potential electrons into the MoFe protein and reduce the active site FeMoco to the substrate binding level. Moreover, this technique allows electrocatalytic activity of the protein to be monitored and the change in redox activity can be correlated directly to the potential. With the same technique, a study of cyanide binding was performed on different variant MoFe proteins of nitrogenase. The redox properties of the isolated cofactor of Mo- and V-dependent nitrogenase were investigated in parallel to the study of the protein-bound cofactors. It was found that FeVco, the active site from V-nitrogenase, exhibited different redox properties compared to that of Mo-nitrogenase. This might account for the unexpected activity in CO reduction that was reported previously for V-nitrogenase.